INVENTORY MODELS INVOLVING LEAD TIME AS A DECISION VARIABLE - unknown (2020)
Most of the literature dealing with inventory problems assumes lead time as prescribed, whether deterministic or probabilistic. In certain cases, lead time can be reduced but at an added cost. In this article we discuss inventory models where lead time is one of the decision variables.